Reducing the gap between the school and university mathematics: university lecturers' perspective - Gruenwald, N; Klymchuk, S; Jovanoski, Z (My University, 2004)
This paper deals with a very practical issue. In many countries there is a gap between school and university mathematics. The transition period from school to university can be hard for many students. Even students with good marks in school mathematics experience psychological difficulties at university and sometimes fail the first year university mathematics courses. Often the pass rate in the first year university mathematics is around 50%. Different parties – school teachers, university lecturers, first year university students, administrators, researchers – might have different views on the reasons for the gap and the ways to narrow or fill it. The purpose of this paper is to present responses of university lecturers worldwide to a short survey concerning the transition period between the school and university mathematics.